A comment on prognostic factors in burns - Ewington, Ian; Torlinski, Tomasz; K. Mullhi, Randeep (Anestezjologia Intensywna Terapia, 2021)
We read the recent paper “Prognostic factors in patients with burns” [1] by Zielinski et al. with great interest. The article is very informative, in a concise and eloquent manner, allowing the reader to familiarise themselves with the plethora of prognostication models used worldwide in the assessment of burn patients. However, reading the paper we noticed that two aspects may require further consideration to provide the reader with a more comprehensive understanding of prognostication in burn patients.